PENDAPAT REMAJA TENTANG PENDIDIKAN SEKS YANG DIBERIKAN OELH ORANG TUA - Zulfaneli Neli; Fuaddillah Putra (Jurnal Counseling Care, 2018)
Sex education is one of the things taboo for some people or a group of people. The purpose of this study is to describe the opinion of adolescents to sex education received from parents, in terms of 1) Sex instruction and 2) education in sexuality. Based on data processing did it was revealed that the opinion of adolescents about sex education provided by parents is very useful for them, this is because it can help them how to maintain the body healthy, especially the reproductive system and how to behave in accordance with the values and norms prevailing in a community environment. Therefore it is expected in the parents and other components of society to be more attention and treat adolescents in accordance with the progress they are living, and guide them by being friends and friends who can understand what they want.